2022
DOI: 10.1038/s41598-022-05414-5
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in paediatric intensive care in England residents: observational study

Abstract: Despite high prevalence of asthma in children in the UK, there were no prior report on asthma admissions in paediatric intensive care units (PICU). We investigated the epidemiology and healthcare resource utilisation in children with asthma presenting to PICUs in England. PICANet, a UK national PICU database, was queried for asthma as the primary reason for admission, of children resident in England from April 2006 until March 2013. There were 2195 admissions to PICU for a median stay of 1.4 days. 59% were mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Children under 15 from poorer areas in the UK make up almost 60% of emergency hospital admissions for asthma and have almost double the risk of needing ventilation, a study in Scientific Reports found 2. It also showed that children from poorer backgrounds accounted for almost 75% of deaths from asthma in paediatric intensive care units.…”
Section: Paediatricsmentioning
confidence: 99%
“…Children under 15 from poorer areas in the UK make up almost 60% of emergency hospital admissions for asthma and have almost double the risk of needing ventilation, a study in Scientific Reports found 2. It also showed that children from poorer backgrounds accounted for almost 75% of deaths from asthma in paediatric intensive care units.…”
Section: Paediatricsmentioning
confidence: 99%
“… 16 A recent study found that 36% of children treated in intensive care units for asthma were from the most deprived neighbourhoods, compared with 11% from the least deprived neighbourhoods. 17 …”
Section: Introductionmentioning
confidence: 99%
“…In the UK, children living in areas of deprivation are more likely to suffer from conditions such as asthma, tooth decay, obesity and diabetes, as well as a higher risk of accidents and accidental death 16. A recent study found that 36% of children treated in intensive care units for asthma were from the most deprived neighbourhoods, compared with 11% from the least deprived neighbourhoods 17…”
Section: Introductionmentioning
confidence: 99%
“…1-4 Asthma also remains an important cause of morbidity later in childhood. 5,6 To reduce childhood asthma morbidity and overtreatment, it is important for clinicians to identify children with asthma early. For this, they require tools that help distinguish preschool children who are at risk of developing asthma from those who cough or wheeze for other reasons and will possibly outgrow their symptoms.…”
Section: Introductionmentioning
confidence: 99%